2021
DOI: 10.1017/s0033291721001306
|View full text |Cite
|
Sign up to set email alerts
|

Trust in government regarding COVID-19 and its associations with preventive health behaviour and prosocial behaviour during the pandemic: a cross-sectional and longitudinal study

Abstract: Background:The effective implementation of government policies and measures for controlling the COVID-19 pandemic requires compliance from the public. This study aimed to examine cross-sectional and longitudinal associations of trust in government regarding COVID-19 control with the adoption of recommended health behaviours and prosocial behaviours, and potential determinants of trust in government during the pandemic.Methods: This study analysed data from the PsyCorona Survey, an international project on COVI… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
203
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 255 publications
(234 citation statements)
references
References 48 publications
10
203
2
1
Order By: Relevance
“…Our manipulation checks indicated that the social worker was seen as more moralistic and more trustworthy than the state secretary. Trust and source credibility have been found before to enhance the effects of health-promoting messages in the context of the COVID-19 pandemic [31][32][33]. In our case, however, the trustworthiness and morality of the sender did not increase overall endorsement to the items, but they did interact with autonomy by unleashing higher variation in pre-to-post rating shifts, perhaps due to the involvement of positive emotions and the reduction in fear [32][33][34].…”
Section: Discussioncontrasting
confidence: 66%
“…Our manipulation checks indicated that the social worker was seen as more moralistic and more trustworthy than the state secretary. Trust and source credibility have been found before to enhance the effects of health-promoting messages in the context of the COVID-19 pandemic [31][32][33]. In our case, however, the trustworthiness and morality of the sender did not increase overall endorsement to the items, but they did interact with autonomy by unleashing higher variation in pre-to-post rating shifts, perhaps due to the involvement of positive emotions and the reduction in fear [32][33][34].…”
Section: Discussioncontrasting
confidence: 66%
“…Uncertainties around the COVID-19 pandemic, and the political-economic context affect public trust in the COVID-19 response and formal and informal healthcare providers. 13 Trust in public health actors is essential for healthcare seeking for COVID-19. The public and expert discourses on COVID-19 are multiple and often conflicting, driving a crisis of legitimacy, trust and uncertainty.…”
Section: Priority 4: Preventative and Health-seeking Behaviourmentioning
confidence: 99%
“…Especially in times of crisis, political trust serves an important function for societal cohesion and compliance. For instance, recent research on the COVID-19 pandemic has demonstrated that citizens with higher political trust are more likely to follow recommendations on social distancing (Bargain and Aminjonov, 2020;Olsen and Hjorth, 2020) and to engage in recommended health behavior (Han et al, 2020). If we want to ensure the stability and smooth functioning of democracy in times of crisis, then, it is of paramount importance to secure the trust of ordinary citizens.…”
Section: Introductionmentioning
confidence: 99%